The Influence of Ethical Leadership on Employee Performance in the Local Government Institution of West Nias - Gulo, Miniyoritasi (ProBisnis : Jurnal Manajemen, 2025)
Ethical leadership is a form of leadership that emphasizes moral values such as integrity, honesty, and responsibility in every action and decision made by a leader. Meanwhile, employee performance can be defined as the outcome of work or activities carried out by individuals based on ethics and applicable rules within an organization. This study employed a survey method by distributing questionnaires to 70 employees working in various local government institutions within the West Nias region. The collected data were then analyzed using simple linear regression to determine the extent to which ethical leadership influences employee performance. Based on the results of the analysis, it was found that ethical leadership has a positive impact and contributes to improving employee performance. These findings indicate that the implementation of ethical principles in leadership plays a significant role in enhancing the quality of work among employees in the West Nias government environment. Therefore, it is strongly recommended that leaders in local government institutions in West Nias continue to uphold ethical leadership principles to achieve better organizational performance.